Nestin and NG2 transgenes reveal two populations of perivascular cells stimulated by photobiomodulation. Issue 4 (17th January 2022) - Gomes, Natália A.; do Valle, Isabella B.; Gleber‐Netto, Frederico O.; Silva, Tarcília A.; Oliveira, Hortência M. de Castro; de Oliveira, Rafaela F.; Ferreira, Luiza de Almeida Q.; Castilho, Lia S.; Reis, Paulo H. R. G.; Prazeres, Pedro H. D. M.; Menezes, Gustavo B.; de Magalhães, Cláudia S.; et al.
Abstract: Pericytes and glial cells are known to collaborate in dental pulp tissue repair. Cell‐based therapies that stimulate these stromal components may be of therapeutic relevance for partially vital dental pulp conditions. This study aimed to examine the early effect of photobiomodulation (PBM) in pericytes from experimentally injured pulp tissue. To accomplish this, we used the Nestin‐GFP/NG2‐DsRed mice, which could allow the identification of distinct pericyte phenotypes. We discovered the presence of two pericytes subsets within the dental pulp, the Nestin + NG2 + (type‐2) and Nestin − NG2 + (type‐1). Upon injury, PBM treatment led to a significant increase in Nestin + cells and pericytes. This boost was mainly conferred by the more committed pericyte subset (NestinNG2 + ). PBM also stimulated terminal blood vessels sprouting adjacent to the injury site while maintaining signs of pulp vitality. In vitro, PBM induced VEGF upregulation, improved dental pulp cells proliferation and migration, and favored their mineralization potential. Herein, different subsets of perivascular cells were unveiled in the pulp tissue. PBM enhanced not only NG2 + cells but nestin‐expressing progenitors in the injured dental pulp. Abstract : Discovery of two perivascular cell phenotypes within the murine pulp tissue. Photobiomodulation led to the stimulation of pericytes and neural progenitors in the injured dental pulp.